طابور الشخصية في نظام العدالة الجنائية السوداني " دراسة مقارنة مع النظام الإنجليزي" - الوليد عبد الحق, الصديق محمود (University of Eloued جامعة الوادي, 2020)
تعتبر شهادة الشاهد بأنَّه رأى بعينه المُتهم يرتكب الجريمة دليل إثبات كافي لإدانته ،ولكي يتم التأكد من مصداقية الشاهد يتم عرض المُشتبه فيه ضمن مجمُوعه يكونو أقرب شبهاً له ، ويقُوم الشاهِد بتحديد الشخص الذي رآه يرتكِب الجرِيمه وذلِك للتأكُد من مِصداقِيته وذلك عبر إجراءات تختلِف مُسمياتِها من مكان لآخر، مثل طابُور العرض أو طابُور الشخصِيّة الحي أو المُباشِر، أوضع صورة للمتهم سواء كانت فوتغرافية أو فيديو، ولكن تظل قيمتة كدلِيل مُنفرد لا تصلح للإدانه في النظام القضائي السوداني والعكس من ذلك النظام الإنجليزي حيث أنه أسهم في إدانة أشخاص أبرياء بسبب أنَّ المحاكم قد أسست الإدانة وفقاً لهذا الدلِيل وحده ، لم يُطوِّر القضاء السُودانِي في المنشُور 40الصادر سنة 1955 الذي يُنظِّم كيفية تعرُّف الشاهِد على المتهم ، بسبب عدم تحدِيثه ليُواكِب الأشكال الحدِيثه للتعرُّف عن طريق الفيديو والذي أثبت أنَّه أيسر في التطبيق من طابُور الشخصية المادِي أو المُباشِر، وقد خرج هذا البحث ببعض الحلول والتوصيات من أجل صياغة قواعد قانُونية مُلزِمة تُواكِب التطوُّر لتطبيقها في الواقع العملي ،منها إستخدام تقنية عرض الفيديو كخيار في إجراء طابور الشخصية وفقا لما هو معمول به في النظام الانجليزي من اجل تحقيق العدالة الجنائية ، ورفع الوعي لدى منسوبي أجهزة العدالة الجنائية بتحاشي أوجُه الخلل التي يُعانِيها دليل طابُور الشخصية. A witness’ testimony that s/he has seen with his own eyes the suspect committing the crime is considered sufficient evidence to convict the suspect. To ensure the credibility of the witness, the suspect is presented among a group of people who look similar to him; then the witness identifies the person that s/he saw committing the crime. This is achieved through procedures that have different names in different places, e.g. Display Lineup or Live Police Lineup, or displaying a photograph or video of the suspect. However, its value, as single evidence, is not valid for conviction in the Sudanese judicial system, as opposed to the English system where the process has contributed to convicting innocent people because courts have based the convictions on this evidence alone. The Sudanese judiciary, in their publication number 40 for the year 1955, which regulates how the witness identifies the accused, did not update the process to keep up with the modern ways of identifying the accused through video, which has proved to be easier in application than the physical or direct police lineup. This research came up with some solutions and recommendations to establish binding legal rules that keep up with the progress and be applied on the ground. These include the technology of video display as an option for the police lineup as applicable in the English system, to achieve criminal justice, raise awareness among criminal justice staff, and avoid the deficiencies experienced in the police lineup’s evidence.
مجلد4، عدد2
Keywords: المشتبه فيه، طابور الشخصية، العدالة الجنائية، شاهد العيان، الجريمة; the suspect, lineups, criminal justice, eyewitness, crime.